Recent advances of antibody-drug conjugates in treating breast cancer with different HER2 status - Yue Qiu; Yaqin Shi; Zhujun Chao; Xinyu Zhu; Yan Chen; Linlin Lu (Therapeutic Advances in Medical Oncology)
Despite the availability of multiple treatment options for breast cancer, challenges such as adverse events, drug resistance, and disease progression persist for patients. The identification of human epidermal growth factor receptor 2 (HER2) as an oncogenic driver in a subset of breast cancers, alongside the development of HER2-targeted therapies, has significantly improved the prognosis of HER2-amplified breast cancers. However, therapeutic options remain limited for HER2-overexpressing or HER2-negative breast cancers. In response to this gap, antibody-drug conjugates (ADCs) have emerged as a promising approach. ADCs combine the specificity of monoclonal antibodies with the cytotoxic effects of chemotherapy, which allows for the targeted delivery of a cytotoxic payload to cancer cells. ADCs have been used as adjuvant chemotherapeutic treatments and salvage therapies across various breast cancer subtypes, which have greatly improved the prognosis of breast cancer patients. Numerous ongoing clinical trials seek to optimize dosing strategies and identify patient populations that would benefit most from ADCs. This review presents an updated and comprehensive overview of emerging investigational ADCs for treating breast cancer patients with various HER2 subtypes. These ADCs are spearheading a new era in targeted cancer therapy, promising to innovate treatment paradigms for both HER2-positive and HER2-low breast cancers.